A Long‐Range Acting Dehydratase Domain as the Missing Link for C17‐Dehydration in Iso‐Migrastatin Biosynthesis. Issue 25 (19th May 2017) - Zhang, Bo; Xu, Zhengren; Teng, Qihui; Pan, Guohui; Ma, Ming; Shen, Ben
Abstract: The dehydratase domains (DHs) of the iso‐migrastatin (iso‐MGS) polyketide synthase (PKS) were investigated by systematic inactivation of the DHs in module‐6, ‐9, ‐10 of MgsF (i.e., DH6, DH9, DH10) and module‐11 of MgsG (i.e., DH11) in vivo, followed by structural characterization of the metabolites accumulated by the mutants, and biochemical characterization of DH10 in vitro, using polyketide substrate mimics with varying chain lengths. These studies allowed us to assign the functions for all four DHs, identifying DH10 as the dedicated dehydratase that catalyzes the dehydration of the C17 hydroxy group during iso‐MGS biosynthesis. In contrast to canonical DHs that catalyze dehydration of the β‐hydroxy groups of the nascent polyketide intermediates, DH10 acts in a long‐range manner that is unprecedented for type I PKSs, a novel dehydration mechanism that could be exploited for polyketide structural diversity by combinatorial biosynthesis and synthetic biology. Abstract : Missed and found : Inactivation of dehydratase (DH) domains of iso‐migrastatin polyketide synthase, followed by in vitro characterization toward substrate mimics with varying chain lengths, identified DH10 as the dedicated dehydratase for elimination of a remote hydroxy group at C17 position during the biosynthesis of iso‐migrastatin. This activity was "missing" in the canonical collinear model.